Sepsis-Induced Takotsubo Cardiomyopathy Leading to Torsades de Pointes - Nirav Patel; Abhishek Shenoy; George Dous; Haroon Kamran; Nabil El-Sherif (Case Reports in Cardiology)
Background. Takotsubo cardiomyopathy (TCM) is sudden and reversible myocardial dysfunction often attributable to physical or emotional triggers. Case Report. We describe a 51-year-old man presented to emergency department with sepsis from urinary tract infection (UTI). He was placed on cefepime for UTI and non-ST-elevation myocardial infarction protocol given elevated troponins with chest pain. Subsequently, patient was pulseless with torsades de pointes (TdP) and then converted to sinus rhythm with cardioversion. An echocardiogram revealed low ejection fraction with hypokinesis of the apical wall. Over 48 hours, the patient was extubated and stable on 3 L/min nasal cannula. He underwent a cardiac catheterization to evaluate coronary artery disease (CAD) and was found to have mild nonobstructive CAD with no further findings. Conclusion. TCM is a rare disorder presenting with symptoms similar to acute coronary syndrome. Though traditionally elicited by physical and emotional triggers leading to transient left ventricular dysfunction, our case suggests that it may also be triggered by a urinary tract infection and lead to severe QT prolongation and a malignant ventricular arrhythmia in TdP.